Nanotubes and nanoparticles based 3D scaffolds for the construction of high performance Biosensors. Issue 1700 (2014) - Singh, Meenakshi; Holzinger, Michael; Tabrizian, Maryam; Cosnier, Serge
ABSTRACT: 3D scaffolds with different pore sizes, using single-walled carbon nanotubes (SWCNTs) and nanoparticles of different size were constructed. Biotinylated glucose oxidase (GOX-B) and anti-cholera toxin (anti-CT) were immobilized onto the one and two level nanoscaffolds, functionalized with pyrene-β-cyclodextrin for the construction of glucose based enzyme sensors and immunosensors, respectively. For enzyme sensors, highest current density and sensitivity (41.72 μA cm -2, 3 mA M -1 cm -2 ) were obtained with two level scaffolds made with 100 nm nanoparticles. In contrast to this, for immunosensors, highest current density and sensitivity (11.71 μA cm -2, 116.2 μA M -1 cm -2 ) were obtained with two level scaffolds made with 500 nm nanoparticles, indicating that the pore sizes can be adjusted using different size of nanoparticles for the respective applications.